Impact of COVID-19 on achieving the goal of sustainable research and education: case of Volgograd State University - Cherkasova, Oksana; Lebskaia, Daria (Journal of Sustainability Perspectives, 2022)
It is of no doubt that the pandemic had and still has a great impact on all the spheres of human activities. The situation has changed the traditional way of life and we have to get used to the new “normality”. Given the unusual and never experienced circumstances, educational institutions all over the world have been forced to establish new ways out and paths to keep the balance and be sustainable. Despite the various obstacles, universities around the globe are still fighting for the SDG 4 and seeking appropriate solutions for achieving this and other goals. Research and education practices have undergone consequential changes which can be positive or negative. In the case of Volgograd State University the authors will try to get the reader acquainted with its best practices that have been implemented to support the students, the faculty and administrative staff during this fluctuating period and go on achieving SDG 4.Keyword: sustainable development, sustainable education, SDG 4, green thinking, green education